2010
DOI: 10.1007/s10194-010-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication of migraine and tension-type headache: summary of the evidence-based recommendations of the Deutsche Migräne und Kopfschmerzgesellschaft (DMKG), the Deutsche Gesellschaft für Neurologie (DGN), the Österreichische Kopfschmerzgesellschaft (ÖKSG) and the Schweizerische Kopfwehgesellschaft (SKG)

Abstract: The current evidence-based guideline on self-medication in migraine and tension-type headache of the German, Austrian and Swiss headache societies and the German Society of Neurology is addressed to physicians engaged in primary care as well as pharmacists and patients. The guideline is especially concerned with the description of the methodology used, the selection process of the literature used and which evidence the recommendations are based upon. The following recommendations about self-medication in migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 102 publications
0
49
0
2
Order By: Relevance
“…However, this guideline was not based on a systematic review. The German evidence-based recommendations for self-medication of migraine and TTH were based on systematic reviews [27], and included only 7 trials that included at least some TTH patients. For self-medication of TTH, it recommended as first-line therapy the fixed-dose combination of acetaminophen, acetylsalicylic acid, and caffeine or the fixed combination of acetaminophen and caffeine as well as monotherapy with ibuprofen or acetylsalicylic acid or diclofenac.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this guideline was not based on a systematic review. The German evidence-based recommendations for self-medication of migraine and TTH were based on systematic reviews [27], and included only 7 trials that included at least some TTH patients. For self-medication of TTH, it recommended as first-line therapy the fixed-dose combination of acetaminophen, acetylsalicylic acid, and caffeine or the fixed combination of acetaminophen and caffeine as well as monotherapy with ibuprofen or acetylsalicylic acid or diclofenac.…”
Section: Discussionmentioning
confidence: 99%
“…Using previous systematic reviews [27,78] and updated searches (to January 2014), 58 reports were identified, 55 from searches and previous reviews, 2 unpublished reports from Reckitt Benckiser [55,56], and 1 clinical trial report with results from clinicaltrials.gov [53]. An additional 6 trials without results were identified on clinicaltrials.gov (Appendix 3).…”
Section: Searchingmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that this cluster mainly includes rather "uncomplicated" migraine patients who seem to be able to self-treat. For these patients, evidence-based guidelines on self-medication are available [14].…”
Section: Discussionmentioning
confidence: 99%